2016
DOI: 10.1016/j.bbr.2015.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Methyl donor supplementation in rats reverses the deleterious effect of maternal separation on depression-like behaviour

Abstract: Adverse early life events are associated with altered stress responsiveness and metabolic disturbances in the adult life. Dietary methyl donor supplementation could be able to reverse the negative effects of maternal separation by affecting DNA methylation in the brain. In this study, maternal separation during lactation reduced body weight gain in the female adult offspring without affecting food intake, and altered total and HDLcholesterol levels. Also, maternal separation induced a cognitive deficit as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…Depleting dietary methyl donor content has been shown to decrease DNA methylation markers in the brain (Pogribny et al ., ), and impede fear memory (Ishii et al ., ; Tomizawa et al ., ). On the other hand, boosting levels of methyl donors (or SAM itself) increases DNA methylation levels in brain (Paternain et al ., ), and elicits antidepressant effects in rats and mice, such as decreased immobility in the FST and improved stress‐induced anhedonia (Czyrak et al ., ; Benelli et al ., ; Brocardo et al ., ; Molina‐Hernandez et al ., ; Paternain et al ., ). This study showed that increasing WKY male rats’ dietary methyl donor content elicited a series of positive behavioral effects including: increased exploratory behavior, increased social interaction and decreased behavioral despair (immobility) in the FST.…”
Section: Discussionmentioning
confidence: 91%
“…Depleting dietary methyl donor content has been shown to decrease DNA methylation markers in the brain (Pogribny et al ., ), and impede fear memory (Ishii et al ., ; Tomizawa et al ., ). On the other hand, boosting levels of methyl donors (or SAM itself) increases DNA methylation levels in brain (Paternain et al ., ), and elicits antidepressant effects in rats and mice, such as decreased immobility in the FST and improved stress‐induced anhedonia (Czyrak et al ., ; Benelli et al ., ; Brocardo et al ., ; Molina‐Hernandez et al ., ; Paternain et al ., ). This study showed that increasing WKY male rats’ dietary methyl donor content elicited a series of positive behavioral effects including: increased exploratory behavior, increased social interaction and decreased behavioral despair (immobility) in the FST.…”
Section: Discussionmentioning
confidence: 91%
“…Depleting dietary methyl donor content has been shown to decrease DNA methylation markers in the brain [89], and impair fear memory [62, 90]. On the other hand, boosting levels of methyl donors (or SAM itself) increases DNA methylation levels in brain [91], and elicits antidepressant effects in rats and mice, such as decreased immobility in the FST and improved stress-induced anhedonia [9295]. Since our methylome profiling data revealed a greater number of hypomethylated genomic regions in brain tissue from adult LR vs. HR rats, we hypothesized that manipulating DNA methylation in LR rats (by altering dietary methyl donor content) could influence aspects of their behavioral phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Since our methylome profiling data revealed a greater number of hypomethylated genomic regions in brain tissue from adult LR vs. HR rats, we hypothesized that manipulating DNA methylation in LR rats (by altering dietary methyl donor content) could influence aspects of their behavioral phenotype. Specifically we predicted: ( a) that supplementing methyl donors in LR rats’ diet (which has been shown to enhance methylation levels in brain [91]) would have antidepressant effects, whereas ( b) depleting dietary methyl donors (which would lower DNA methylation levels in the brain [89]) would exacerbate LRs’ anxiety/depression-like phenotype. We found that, indeed, depleting dietary methyl donor content worsened LRs’ depression-like behavior (immobility) in the FST.…”
Section: Discussionmentioning
confidence: 99%
“…13 Conversely, maternal deprivation caused considerable stress to both dams and their pups. 21,22 The differences in these two models may be associated with differences in maternal care because in the present model, the dams continued to groom and lick their pups.…”
Section: Discussionmentioning
confidence: 76%